Estimating Extreme Geoelectric Field Values for the Australian Region - Richard Marshall; Léna Dziura; Liejun Wang; Jeanne Young; Michael Terkildsen (Space Weather)
Abstract There are a number of global initiatives to understand and mitigate the impacts of extreme space weather on critical infrastructure and modern society. This paper provides the results of an analysis to estimate extreme geoelectric field values for the Australian region to facilitate evaluation of Australia's power system response to extreme geomagnetic storms. Geoelectric fields are calculated using a grid of modeled magnetotelluric impedance tensors obtained from a 3‐D conductivity model of the Australian region. Statistical metrics derived from grids of geoelectric field time series are analyzed as a function of Dst index for different storm days to extrapolate geoelectric fields to extreme storm levels over a range of ground conductivity conditions. For Carrington event storm levels, geoelectric field values of 5.3 ± 3.8 V/km in the north‐south direction and 9.6 ± 4.3 V/km in the east‐west direction are expected for areas of electrically resistive rocks near coastlines that are adjacent to deep highly conductive oceans, and inland, where there are large contrasts between the electrical conductivities of different rock types across Australia. Further, geoelectric field values may change by at least an order of magnitude over the grid spacing interval of 50 km in these areas. The results of the analysis also suggest that upscaling grids of geoelectric field time series derived from an observed storm by the ratio of extreme storm Dst to the observed storm Dst are a valid approach for the Australian region that provides extreme storm scenarios for different storm morphologies.